2010
DOI: 10.1111/j.1365-246x.2009.04490.x
|View full text |Cite
|
Sign up to set email alerts
|

Dynamic mantle density heterogeneities and global geodetic observables

Abstract: S U M M A R YWe investigate the influence of mantle dynamics on low degree deformations of the Earth at geological timescale. We first compute surface deformations, and discuss the analytical form of the tangential surface displacement induced by internal loads, in a reference frame related to the centre of mass of the planet. We use the theoretical Love numbers formalism since the Earth has a viscoelastic behaviour at geological timescale.Then we quantify degree-one and degree-two deformations induced by upwe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
14
0

Year Published

2011
2011
2017
2017

Publication Types

Select...
6
2

Relationship

2
6

Authors

Journals

citations
Cited by 21 publications
(15 citation statements)
references
References 44 publications
(66 reference statements)
1
14
0
Order By: Relevance
“…They separated the origin drift error and geocenter velocity and found respectively −0.5 mm/a and −0.8 mm/a (for both GIA and PDMT) [ Wu et al , 2011; X. Wu, personal communication, 2012] equivalent to 1.3 mm/a in total for T˙Z . However, we note that the first value depends on OBP and GRACE data and the second is in the upper limit of other published values [ Greff‐Lefftz et al , 2010; Métivier et al , 2010]. As a consequence, we prefer estimating in the following our own ORB as an independent study.…”
Section: Itrf2008‐pmm and The Frame Originmentioning
confidence: 53%
“…They separated the origin drift error and geocenter velocity and found respectively −0.5 mm/a and −0.8 mm/a (for both GIA and PDMT) [ Wu et al , 2011; X. Wu, personal communication, 2012] equivalent to 1.3 mm/a in total for T˙Z . However, we note that the first value depends on OBP and GRACE data and the second is in the upper limit of other published values [ Greff‐Lefftz et al , 2010; Métivier et al , 2010]. As a consequence, we prefer estimating in the following our own ORB as an independent study.…”
Section: Itrf2008‐pmm and The Frame Originmentioning
confidence: 53%
“…3 and 4. Historical geocenter motion due to n = 1 internal load-induced deformation has also been studied over even longer time scales using the Maxwell viscoelastic theory (Greff-Lefftz and Legros, 1997;Greff-Lefftz et al, 2010).…”
Section: Viscoelastic Earth Deformationmentioning
confidence: 99%
“…This unique, very long-wavelength component is important (critically so in many cases) for understanding global mass redistribution processes such as sea level rise, atmospheric and ocean circulation, present-day ice mass imbalance, continental hydrology, ocean tides, glacial isostatic adjustment (GIA), and geodynamic processes of the Earth's core and mantle (e.g., Stolz, 1976;Trupin et al, 1992;Dong et al, 1997;Greff-Lefftz andLegros, 1997, 2007;Watkins and Eanes, 1997;Chen et al, 1999;Blewitt et al, 2001;Wu et al, 2002;Blewitt and Clarke, 2003;Chambers et al, 2004;Klemann and Martinec, 2009;Greff-Lefftz et al, 2010).…”
Section: Introductionmentioning
confidence: 99%
“…We recall that there is a significant Z-translation rate of 1.8 mm/yr between ITRF2000 and ITRF2005 . A few studies (Greff-Lefftz 2000;Greff-Lefftz et al 2010;Métivier et al 2010) have shown that geophysical phenomena, such as present day ice melting or postglacial rebound, cannot lead to an increase of the geocenter velocity along the Z-axis larger than 0.3 mm/yr in a decade. Given the fact that the ITRF2008 results show negligible translation rates with respect to ITRF2005, the Z-translation rate between ITRF2005 and ITRF2000 is most likely an indication of an imprecise origin determination of the ITRF2000 solution.…”
Section: Itrf2008 Originmentioning
confidence: 99%